Komunikasi Diagonal Pegawai Telkom Bandung dalam Melakukan Program Reverse Coach - Zhafira Indah Widiharjanti; Dede Lilis Chaerowati (UNISBA Press, 2023)
Abstract. The SSOP (Shared Service Operation and Procurement) Unit of Telkom Bandung has a routine activity program that is carried out every two weeks called Reverse Coach. This program aims to increase harmony between employees and also aims to exchange information from younger employees to more senior employees so they can keep up with the times and technology so they stay up to date. In implementing the Reverse Coach program, SSOP unit employees use diagonal communication. The purpose of this research is to find out the process of diagonal communication, the reasons for implementing diagonal communication, the inhibiting factors and the solutions chosen by the SSOP Telkom Bandung unit in implementing the Reverse Coach program. This study uses a qualitative research method by applying a case study approach and a constructivist paradigm. The theory used in this study is the theory of human relations. Conducting interviews, observations, and documentation for data collection techniques. The analysis technique uses interactive analysis techniques from Miles & Huberman namely data reduction, data presentation, and conclusion/verification. To test the validity of the data used in this study by applying the dependability test and triangulation method.The results of this study are that the diagonal communication implemented in the Reverse Coach program can create and increase harmony among SSOP unit employees, can increase employee understanding of technology or the company, is effective and efficient in exchanging information, can increase work productivity, and can increase collaboration between employee. Abstrak. Unit SSOP (Shared Service Operation and Procurement) Telkom Bandung memiliki suatu program kegiatan rutin yang dilakukan setiap dua minggu sekali bernama Reverse Coach. Program ini bertujuan untuk meningkatkan keharmonisan antar pegawai dan juga bertujuan untuk saling bertukar informasi dari pegawai muda kepada pegawai yang lebih senior agar bisa mengikuti perkembangan jaman dan teknologi sehingga tetap up to date. Dalam pelaksanaan program Reverse Coach, para pegawai unit SSOP menggunakan komunikasi diagonal. Tujuan diadakannya penelitian ini adalah untuk mengetahui proses komunikasi diagonal, alasan penerapan komunikasi diagonal, faktor penghambat serta solusi yang dipilih oleh unit SSOP Telkom Bandung dalam pelaksanaan program Reverse Coach. Penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi kasus serta menggunakan paradigma konstruktivis. Teori yang digunakan dalam penelitian ini adalah teori hubungan manusiawi. Melakukan wawancara, observasi, dan dokumentasi untuk teknik pengumpulan data. Teknik analisis menggunakan teknik analisis interaktif dari Miles & Huberman yakni reduksi data, sajian data, dan penarikan kesimpulan/verifikasi. Untuk uji keabsahan data yang digunakan dalam penelitian ini adalah uji dependabilitas dan triangulasi metode. Hasil dari penelitian ini adalah komunikasi diagonal yang diterapkan dalam program Reverse Coach dapat menciptakan dan menigkatkan keharmonisan antar pegawai unit SSOP, dapat meningkatkan pemahaman para pegawai mengenai teknologi ataupun perusahaan, efektif dan efisien dalam pertukaran informasi, dapat meningkatkan produktivitas kerja, dan dapat meningkatkan kolaborasi antar pegawai.